Efek Antihiperurisemia Ekstrak Etanol Daun Pandan (Pandanus Amaryllifolius ) Pada Mencit (Mus Musculus) - Widysusanti Abdulkadir; Dizky Ramadani Putri Papeo; Juliyanty Akuba; Andi Makkulawu (Journal Syifa Sciences and Clinical Research, 2022)
Hyperuricemia is a condition in which the kidneys fail to excrete uric acid, resulting in high levels of uric acid. (Kaneko et al., 2014). Uric acid will be excreted into the kidneys along with urine. The decrease of uric acid secretion into the kidney tubules due to interference of uric acid elimination to the kidneys which causes uric acid levels in the blood to increase (Ningtiyas Ramadhian, 2016). An adult male is suffering from hyperuricemia when his serum uric acid level is more than 7.0 mg/dl, while hyperuricemia in adult women occurs when the serum uric acid level is above 6.0 mg/dl. Hyperuricemia therapy management in the community is very diverse, ranging from traditional medicines and synthetic drugs. One of the traditional plants used as traditional medicine is pandan leaves. This study aimed to determine the anti-hyperuricemia effect of ethanol extract of Pandanus amaryllifolius leaves on mice (Mus musculus L.). The study involved 25 male mice which were divided into 5 groups; each group consisted of five male mice. Group I was a negative control with Na-CMC 1% w/v, while Group II was a positive control with Allopurinol 0.117 g w/v. Further, Groups III, IV, and V were given Ethanol Extract of 0.5 gr w/v, 1 g w/v, 1.5 g w/v of Pandan Leaves, respectively. The results showed that there was no significant decrease in uric acid levels in group I. Meanwhile, Groups II, III, IV, and V showed a significant reduction in uric acid levels with identical effectiveness. The results of the study were then tested using the One-Way ANOVA statistical test; the p-value was 0.01 (α 0.01). The best dose was 1.5 g of extract since there was a significant difference from the pandan leaves extract with 1.5 g (p 0.01). In conclusion, pandan leaves extract can reduce uric acid levels in the blood. This was evidenced by a decrease of 4.1 mg/dl in uric acid levels in mice during the experiment.